2017
DOI: 10.1016/j.cell.2017.10.040
|View full text |Cite
|
Sign up to set email alerts
|

A J-Protein Co-chaperone Recruits BiP to Monomerize IRE1 and Repress the Unfolded Protein Response

Abstract: SummaryWhen unfolded proteins accumulate in the endoplasmic reticulum (ER), the unfolded protein response (UPR) increases ER-protein-folding capacity to restore protein-folding homeostasis. Unfolded proteins activate UPR signaling across the ER membrane to the nucleus by promoting oligomerization of IRE1, a conserved transmembrane ER stress receptor. However, the coupling of ER stress to IRE1 oligomerization and activation has remained obscure. Here, we report that the ER luminal co-chaperone ERdj4/DNAJB9 is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
202
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(208 citation statements)
references
References 61 publications
3
202
2
1
Order By: Relevance
“…Interestingly, Hu et al (63) observed that newly synthesized BiP is more susceptible to SubAB, raising the possibility that the IRE1a-bound BiP is indeed the newly synthesized protein. Another relevant mechanism maybe the recruitment of a complex of BiP with the cochaperone ERdj4, which was shown to mediate monomerization of IRE1a (64). The availability of this complex may be altered when some BiP is ablated, or perhaps its recruitment to inactive IRE1a is insufficient to limit cluster size.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Hu et al (63) observed that newly synthesized BiP is more susceptible to SubAB, raising the possibility that the IRE1a-bound BiP is indeed the newly synthesized protein. Another relevant mechanism maybe the recruitment of a complex of BiP with the cochaperone ERdj4, which was shown to mediate monomerization of IRE1a (64). The availability of this complex may be altered when some BiP is ablated, or perhaps its recruitment to inactive IRE1a is insufficient to limit cluster size.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating misfolded proteins in the ER lumen engage BiP thus releasing the three sensors. A FRET UPR induction assay, developed to quantify the association and dissociation of the IRE1 luminal domain from BiP upon ER stress , demonstrated that the ER luminal co‐chaperone ERdj4/DNAJB9 represses IRE1 by promoting a complex between BiP and the luminal stress‐sensing domain of IRE1α . Moreover, it has recently been reported that another ER luminal chaperone, Hsp47, displaces BiP from the IRE1 UPRosome to promote its oligomerization .…”
Section: Er Stress Consequencesmentioning
confidence: 99%
“…IRE1α dimerization can be evaluated by detecting the foci formation of IRE1α-GFP [26] and BiFC assay [27]. Recently, Amin-Wetzel et al also established a new method to measure the endogenous IRE1α dimerization in cells [28]. Newbatt et al reported a DELFIA technology that is specific for detecting IRE1α autotransphosphorylation [29].…”
Section: Discussionmentioning
confidence: 99%